Acute and Chronic Workload Ratios of Perceived Exertion, Global Positioning System, and Running-Based Variables Between Starters and Non-starters: A Male Professional Team Study - Nobari, Hadi; Alijanpour, Nader; Martins, Alexandre Duarte; Oliveira, Rafael (Frontiers in Psychology, 2022)
The study aim was twofold i) to describe and compare the in-season variations of acute: chronic workload ratio (ACWR) coupled, ACWR uncoupled, and exponentially weighted moving average (EWMA) through session rated perceived exertion (s-RPE), total distance (TD), high-speed running distance (HSRD), and sprint distance across different periods of a professional soccer season (early, mid and end-season) between starters and non-starters; ii) to analyze the relationship the aforementioned measures across different periods of the season for starters and non-starters. Twenty elite soccer players. They were divided into starter and non-starter groups and were evaluated for 20 weeks. ACWR had general changes throughout the season. At the beginning and end of the mid-season, the highest ACWR was observed in three parameters: s-RPE, TD, and HSRD. ACWR and EWMA through sprint distance were higher at the beginning of the Early-Season than at any other time of the season. The ACWR coupled of s-RPE shows a significant higher value for non-starters than starters (p= 0.015; g= -1.01 [-1.98, -0.09]) and the ACWR coupled of TD shows a significant higher value for starters than non-starters in early-season (p< 0.01; g= 3.01 [1.78, 4.46]), and shows a significant higher value for non-starters than starters in mid-season (p< 0.01; g= -2.52 [-3.83, -1.39]), and end-season (p< 0.01; g= -2.57 [-3.89, -1.43]). While the EWMA of TD shows a significant higher value for starters than non-starters in early-season (p< 0.01; g= 2.25 [1.17, 3.49]) and mid-season (p< 0.01; g= 2.42 [1.31, 3.71]), and shows a significant higher value for non-starters than starters in end-season (p< 0.01; g= -2.23 [-3.47, -1.16]). Additionally, we found some correlations between external and internal load measures during three periods of the in-season. In addition, the necessary work for non-starter players' improvement is not done during training, and these players lose their readiness as the season progresses. Consequently, these players perform poorly during the match. Therefore, coaches and their staff should consider devising new activities to keep non-starter players physically fit.